HUBUNGAN TINGKAT KECEMASAN DAN BODY IMAGE DENGAN POLA MAKAN PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Ranis Puspitasari (2020)
College students are categorized as a period between childhood and adulthood, who have very high levels of anxiety and prioritized ideal body shape. This can affect a person's eating pattern, especially in women. This research was conducted to determine the correlation between anxiety level and body image with eating pattern of medical students at Universitas Pembangunan Nasional Veteran Jakarta. This research was an analytical observational with cross sectional design. A simple random sampling technique was used to collect data from as many as 104 famale students. Measurement of anxiety level was carried out using the Hamilton Anxiety Rating Scale (HARS) and body image using the Figure Rating Scale (FRQ) questionnaire and eating pattern using the eating pattern scale. The Chi Square test with the confidence internal of 95% was used to analyze data statistically. Result showed that there was significant correlation between anxiety level with eating pattern with significance value of p =0,000 (p <0,05) and there was no significant correlation between body image with eating pattern with significance value of p =0,248 (p >0,05). Multivariate test showed that anxiety level had more dominant relation with body image. There was a correlation between anxiety levels with eating pattern and there was no correlation between body image with eating pattern.